2022
DOI: 10.3390/ijerph19063560
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Excessive Screen Time among Children under Five Years Old in Selangor, Malaysia: A Cross-Sectional Study

Abstract: Excessive screen time interferes with the health and development of children. However, the screen time situation among Malaysian children remains poorly understood. This study aims to identify the prevalence and determinants of excessive screen time among children under five years in Selangor, Malaysia, using the latest World Health Organization guidelines. In this cross-sectional study, 489 parent–child dyads were randomly selected from nine government health clinics in Petaling district, Selangor. Total scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Generally, parents play three key roles in young children’s digital usage, as facilitators, teachers, and gatekeepers [ 74 ]. Parents’ digital usage and their perception and mediation of young children’s digital usage jointly influence young children’s digital use and well-being [ 75 ]. First, parental digital usage affects young children’s digital usage.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, parents play three key roles in young children’s digital usage, as facilitators, teachers, and gatekeepers [ 74 ]. Parents’ digital usage and their perception and mediation of young children’s digital usage jointly influence young children’s digital use and well-being [ 75 ]. First, parental digital usage affects young children’s digital usage.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive screen time in preschool children is associated with delay in speech development, lack of physical activity, obesity, attention deficit and hyperactivity, and decrease in cognitive functions (21)(22)(23). A rise in screen time has been observed in preschool children during the coronavirus pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…We found that two factors contributed to school-age children’s screen time, with the largest coefficient of quantification of the number of electronic items in the home, followed by parental screen time. A parental screen time greater than 2 h per day was the determining factor for children’s screen time [ 43 ]. A study in Fiji found that approximately 24% believed there was no negative impact on children due to screen time and more than half (56%) of the parents (or caregiver guardians) thought that screen time for children below the age of 2 years actually has positive consequences on children.…”
Section: Discussionmentioning
confidence: 99%